Answer:
![a_6_3=371](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wnh47clqo42o43wv9nrkcot75tixb4ck7r.png)
Explanation:
we know that
In an Arithmetic Sequence the difference between one term and the next is a constant and this constant is called the common difference
we have
![-1,5,11,...](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5jo73rg4fptoeyhaxakjakzjhh1w8zjap4.png)
Let
![a_1=-1\\a_2=5\\a_3=11](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zjmfz05io2cuw4c3ceuxbhr1t83z4uc5we.png)
![a_2-a_1=5-(-1)=5+1=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ga5rzv0neyapxxn6ucgkpob8ebyi9sx3jg.png)
![a_3-a_2=11-5=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5ndqjpcnk4kn7ucg0k5vdkvkcqhzhuijzz.png)
The common difference is
![d=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/klc1nci0s5nzu6hgfklanefzb5klzv1qil.png)
We can write an Arithmetic Sequence as a rule
![a_n=a_1+d(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ubsa8ruizynnpnuo1w20syq2ij3srxp658.png)
where
a_n is the nth term
d is the common difference
a_1 is the first term
n is the number of terms
Find the 63rd term of the arithmetic sequence
we have
![n=63\\d=6\\a_1=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ltduv5vvoj8d2lldkx15o9rjt6fifcim9e.png)
substitute
![a_6_3=-1+6(63-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/58la8eln4rg99s6z9ufwz6wad36h97uvl8.png)
![a_6_3=-1+6(62)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1nu6s7qd6cpz7k80d35rn6fauvcqfr78tk.png)
![a_6_3=-1+372](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hyhtgbnzwljen3baklyezh3d3z0kcyi7ow.png)
![a_6_3=371](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wnh47clqo42o43wv9nrkcot75tixb4ck7r.png)